Reading Romantic poetry - Stafford, Fiona J. (Hoboken, NJ : John Wiley & Sons, 2012)
Reading Romantic Poetry introduces the major themes and preoccupations, and the key poems and players of a period convulsed by revolution, prolonged warfare and political crisis. Provides a clear, lively introduction to Romantic Poetry, backed by academic research and marked by its accessibility to students with little prior experience of poetryIntroduces many of the major topics of the age, from politics to publishing, from slavery to sociability, from Milton to the mind of manEncourages direct responses to poems by opening up different aspects of the literature and fresh approaches to readin.
Front Matter -- The Pleasures of Poetry -- Solitude and Sociability -- Common Concerns and Cultural Connections -- Traditions and Transformations: Poets as Readers -- Reading or Listening? Romantic Voices -- Sweet Sounds -- Poems on Pages -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: 1800-1899; English poetry -- 19th century -- History and criticism; Romanticism -- Great Britain; POETRY -- English, Irish, Scottish, Welsh; English poetry; Romanticism; Great Britain; Electronic books; Criticism, interpretation, etc